SOSIALISASI PENGEMBANGAN UMKM DI DUSUN KALANGAN KEBONAGUNG IMOGIRI BANTUL - Suyanto Suyanto; Uum Helmina Chaerunisak; Bernadetta Diansepti Maharani; Intan Wulandari; Rfanurhidayati (ABDIMAS DEWANTARA, 2022)
The implementation of this community service activity involves MSME actors, especially in Padukuhan, Kalangan, Kebonagung, Imogiri, Bantul. Many of the Padukuhan communities are MSME actors. Therefore, after conducting a survey on the conditions and situation in the hamlet of Kalangan, it can be concluded that MSME actors need knowledge about MSME management. The purpose of this activity is to explain digital marketing strategies, simple bookkeeping management, and knowledge of taxation in MSMEs. The method used is the lecture and discussion method. The materials presented at this community service were digital marketing strategies, simple bookkeeping management and tax knowledge on MSMEs and current developments. The results of this activity are digital marketing strategies and MSME bookkeeping management that can be a source of reference for MSME participants or actors. The presentation from the speaker received a positive response and was easy to apply to the MSME business in Padukuhan Kalangan Kebonagung, Imogiri, Bantul. Keywords: MSMEs, Digital Marketing, Taxation, Simple Bookkeeping.